ANALISIS EFISIENSI PG WATOETOELIS KABUPATEN SIDOARJO - Diar Iswardhani; Rudi Wibowo; Anik Suwandari (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2016)
Cane is a plant which splits into one piece (monocots), including the grassy plants (Nartheciaceae). Its stalk is 3-5m tall, the stems are segmented and grained, the leaves sit on each segment and the Cane grows in tropical area. The objectives of the study were (1) to determine the quality of milled cane in PG Watoetoelis, (2) to know the production cost of sugar at PG Watoetoelis, and (3) to determine the technical efficiency of PG Watoetoelis. The method of determining area of ​​the research was conducted purposively (purposive methods). The research method used was descriptive quantitative method. This study used secondary data of 2009-2013 owned by PG Watoetoelis and other institutions as supporting data. The results showed that (1) the sugar factory, PG Watoetoelis, was not technically efficient in 2009 - 2013. It can be seen from the average of technical efficiency parameter numbers over 5 years was still under the standard; the value of ME 86.03%, OR 80.97%, pol 9.58%, yield 6.76%, and the value of BHR with a value of 96.06% which was above the standard, (2) the quality of the raw materials at PG Watoetoelis in 2009-2013 had low quality. It can be seen from the standard average value in the last 5 years that the value of sap was 73.10%, pol 9.58%, and NPP 10.17. The value for the quality of the sugar cane was below standard; 80-83% for sap, ≥ 12.0% for pol and ≥ 14.00 for NPP, and (3) the cost of production (BPP) at PG Watoetoelis in 2010- 2013 was inefficient, because it was above the standard of BPP. The value of BPP at PG Watoetoelis in 2010 - 2013 was Rp 6.874 kg, Rp. 7.696/kg, Rp. 8.830/kg, and Rp. 8.931/kg, while the standard of BPP Rp 6,350/kg, Rp 7,000/kg, Rp 8,100/kg and Rp 8,500/kg.